#TITLE_ALTERNATIVE# - (NIM 13205015); Pembimbing: Dr.Ir. Pekik Argo Dahono, NOPIANSYAH
Analysis and minimization of output current's harmonics of three-level PWM inverter is proposed. The analytical expressions for the output current's harmonics as a function of the PWM reference signal is derived. It is shown that, the reference signal which produces a minimum output current's harmonic of three-level PWM inverter is sinusoidal signal added with 25 percent of third harmonic. The result is same with the previously research in the three-phase PWM inverter with two-level output voltage. Simulation results are presented to show the validity of the proposed analysis method.